Application of Critical Path Method and Fuzzy Logic in Optimizing Bottled Drinking Water Production - Wanda Wira Yudiarti; Faiz Ainur Razi (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2021)
AbstractProject management is one of the analytical techniques used for planning, scheduling, and making decisions about activities. This is useful so that the project can be implemented optimally and efficiently. Project management can be done by optimizing the network. Network optimization is very important for the production of bottled drinking water (AMDK)